Modulatory role of welding fumes on serum zinc and copper levels and oxidative stress markers among welders: Considering smoking as a possible implication - Bartholomew Chukwuebuka Nwogueze; Mary Isioma Ofili; Ugochukwu E. Uzuegbue; Deliverance Brotobor; Njideka Judith Esievo (Toxicology Reports, 2024)
The presence of heavy metals in welding fumes and the numerous metals that make up welding gases expose welders to numerous occupational dangers, including major occupational health issues worldwide. The gases from welding are a significant and highly skilled process that have a considerable negative impact on welders' overall health and wellbeing. This study evaluated the influence of welding fumes on serum zinc and copper levels and oxidative stress biomarkers in welders considering smoking as a potential risk factor. The study used a case-control experimental design. Forty (40) healthy adult males were randomly selected comprising twenty (20) in the experimental group involving smokers and nonsmokers with welding experience and twenty (20) in the control group involving smokers and nonsmokers without welding experience. Data are expressed as the mean±SEM, and comparisons of means across groups were performed using one-way ANOVA, followed by Turkey's multiple comparisons test. The results showed that the serum zinc and copper levels of smokers were significantly (p < 0.05) increased in comparison to the control group, and a graded increase in the serum GST and MDA levels was observed across groups. The serum SOD level of smoker nonwelders was significantly (p < 0.05) increased when compared with the control group. Smokers who did not weld had significantly (p < 0.05) higher serum SOD levels. The results likewise showed a statistically nonsignificant reduction in glutathione levels and a substantial decrease in total antioxidant capacity (TAC) in the experimental group. Overall, changes in the antioxidant parameters showed that smoking and welding fumes can exacerbate an increase in the activity of reactive oxygen species (ROS), resulting in deteriorated health conditions.